Predictive role of emotional intelligence and individual occupational factors on occupational stress among the midwives working in health centers and hospitals in Rasht, 2018 - Mahnaz Niknejad Talemi; Fatemeh Ranjkesh; Mehdi Ranjbaran; Nasim Bahrami (Tehran University of Medical Sciences, 2020)
Background & Aim: Midwives experience high levels of stress due to the nature of their work. Some factors can play a significant role in the occupational stress experience. The aim of the study was to investigate the predictive role of emotional intelligence and individual-occupational factors on occupational stress among the midwives working in Rasht. Methods & Materials: In this descriptive, correlational study, 250 midwives working in health centers and hospitals in Rasht, from May to September 2018 were included using stratified random sampling. Questionnaires on demographic characteristics, emotional intelligence and occupational stress were used to collect the data. Data were analyzed through the SPSS software version 23 using descriptive and inferential statistics including independent t-test, one-way ANOVA, Pearson correlation, multiple linear regression at the significant level of 0.05. Results: The mean and standard deviation of emotional intelligence and occupational stress were 114.20±12.55, 119.66±15.48 respectively. Predictors of occupational stress (P<0.05) included workplace variables (private hospital: β=-0.19, P=0.012), overtime hours (β=-0.33, P<0.001), sleeping hours (β=0.13, P=0.011), social activity (β=0.11, P=0.029), age (β=0.25, P=0.045) and the overall score of emotional intelligence (β=0.55, P<0.001). These variables explained 54% of variance of occupational stress. Conclusion: Overall, in the adjusted model of the workplace variables, overtime hours, sleeping hours, level of social activity, midwife's age and the overall score of emotional intelligence were significant predictors of occupational stress. Accordingly, designing effective programs can improve the performance of midwives.